THE APPLICATION OF TEAMS-GAMES-TOURNAMENT (TGT) TO INCREASE STUDENTS’ ACTIVENESS AND LEARNING OUTCOMES - Putri, Dewi Siswanti; Mawardi, Mawardi (Universitas Pendidikan Ganesha, 2017)
This study was aimed at improving the activeness and learning outcomes of 5th grade students of SDN Jetak 03 Getasan District of Semarang Regency with the application of Teams-Games-Tournament (TGT) model. This study was applied to 5th graders with 18 students as subject and using spiral model from C. Kemmis & Mc Taggart in 2 cycles. Data collection techniques used was test and non-test techniques. Results show that there was an increase from cycle I and cycle II, in both students’ activeness and student learning outcomes. Therefore, TGT model can be used to increase students’ activeness and learning outcomes.